Cardiac sarcoidosis-state of the art review - Hulten, Edward; Aslam, Saira; Osborne, Michael; Abbasi, Siddique; Bittencourt, Marcio Sommer; Blankstein, Ron (Cardiovascular diagnosis and therapy, 2016)
Sarcoidosis is a multi-system inflammatory disorder of unknown etiology resulting in formation of non-caseating granulomas. Cardiac involvement-which is associated with worse prognosis-has been detected in approximately 25% of individuals based on autopsy or cardiac imaging studies. Nevertheless, the diagnosis of cardiac sarcoidosis is challenging due to the low yield of endomyocardial biopsy, and the limited accuracy of various clinical criteria. Thus, no gold standard diagnostic criterion exists. This review will summarize the pathophysiology, diagnosis, and treatment of cardiac sarcoidosis with a focus on advanced cardiovascular imaging, We review the evidence to support a role for cardiac magnetic resonance (CMR) imaging in the initial evaluation of selected patients with suspected cardiac sarcoidosis, with cardiac positron emission tomography (PET) as an alternative or complementary initial diagnostic test in a subgroup of patients in whom CMR may be contra-indicated or when CMR is negative with continued clinical concern for myocardial inflammation. In addition to the diagnostic value of these tests, CMR and PET are also useful in identifying patients who have higher risk of adverse events such as ventricular tachycardia or death, in whom preventive therapies such as defibrillators should be more strongly considered. Although no randomized controlled trials for treatment of cardiac sarcoidosis exist, immunosuppressive therapy is often used. We review emerging evidence regarding the use of cardiac PET to identify and quantity the amount of myocardial inflammation as well as to guide the use of immunotherapy. Future studies are needed to determine the benefit of imaging guided therapies aimed at improving patient outcomes.